Prevalence, clinical characteristics, and management of irritable bowel syndrome in Vietnam: A scoping review - Duc Trong Quach (Wiley, 2021)
Abstract Irritable bowel syndrome (IBS) is one of the most common gastrointestinal disorders worldwide. Its prevalence varies significantly from country to country, largely due to heterogeneity in the available data. Recent studies show that the prevalence of IBS in Asia is on the rise. However, there are very limited data regarding its prevalence in the Vietnamese population. This review aims to offer an overview of the prevalence and clinical characteristics of IBS in the Vietnamese population; and to discuss the current management of IBS in Vietnam—taking into account the available medical resources and the local spectrum of lower gastrointestinal disorders that may mimic IBS.